A new method for CT dose estimation by determining patient water equivalent diameter from localizer radiographs: Geometric transformation and calibration methods using readily available phantoms. Issue 7 (1st June 2018) - Zhang, Da; Mihai, Georgeta; Barbaras, Larry G.; Brook, Olga R.; Palmer, Matthew R.
Abstract : Purpose: Water equivalent diameter (Dw) reflects patient's attenuation and is a sound descriptor of patient size, and is used to determine size‐specific dose estimator from a CT examination. Calculating Dw from CT localizer radiographs makes it possible to utilize Dw before actual scans and minimizes truncation errors due to limited reconstructed fields of view. One obstacle preventing the user community from implementing this useful tool is the necessity to calibrate localizer pixel values so as to represent water equivalent attenuation. We report a practical method to ease this calibration process. Methods: Dw is calculated from water equivalent area (Aw) which is deduced from the average localizer pixel value ( LPV ) of the line(s) in the localizer radiograph that correspond(s) to the axial image. The calibration process is conducted to establish the relationship between Aw and LPV . Localizer and axial images were acquired from phantoms of different total attenuation. We developed a program that automates the geometrical association between axial images and localizer lines and manages the measurements of Dw and average pixel values. We tested the calibration method on three CT scanners: a GE CT750HD, a Siemens Definition AS, and a Toshiba Acquilion Prime80, for both posterior–anterior (PA) and lateral (LAT) localizer directions (for all CTs) and with different localizer filters (for the Toshiba CT). Results: The computer program was able to correctly perform the geometrical association between corresponding axial images and localizer lines. Linear relationships between Aw and LPV were observed (with R 2 all greater than 0.998) on all tested conditions, regardless of the direction and image filters used on the localizer radiographs. When comparing LAT and PA directions with the same image filter and for the same scanner, the slope values were close (maximum difference of 0.02 mm), and the intercept values showed larger deviations (maximum difference of 2.8 mm). Water equivalent diameter estimation on phantoms and patients demonstrated high accuracy of the calibration: percentage difference between Dw from axial images and localizers was below 2%. With five clinical chest examinations and five abdominal‐pelvic examinations of varying patient sizes, the maximum percentage difference was approximately 5%. Conclusions: Our study showed that Aw and LPV are highly correlated, providing enough evidence to allow for the Dw determination once the experimental calibration process is established.